Directional solidification of Al-Cu-Si-Mg quaternary eutectic alloy - Kaygisiz, Yusuf; Marasli, Necmettin (ELSEVIER SCIENCE SA, 2017)
The effects of growth rates on the microstructure, microhardness, tensile strength, and electrical resistivity were studied in directionally solidified Al-Cu -Si -Mg (A1-28 wt%Cu-6wt.%Si-2.2 wt%Mg) quaternary eutectic alloy. The directional solidification process was carried out at five different growth rates (V = 9.63-173.5 mu m/s) at a constant temperature gradient (G = 6.88 Kimm). The microstructure of the directionally solidified Al-Cu-Si-Mg quaternary eutectic alloy consists of Al solid solution, irregular Si plates, and intermetallic Al2Cu (theta) and Cu2Mg8Si6Al5 (Q) phases with honeycomb morphology. The dependencies of lamellar spacing, microhardness, tensile strength, and electrical resistivity on growth rates were found to be lambda(CuAl2) = 19.05 V-041, lambda(Cu2Mg8Si6Al5) = 51.28 V-0.43, lambda(si) = 8.74 V-0.46, HV = 170.7 + 79.08V(0.25), HV = 237.68(V)(0.043) sigma = 343.45(V)(0.15), and rho = 3.42 x 10(-8)(V)(0.10) orespectively, for the Al-Cu-Si-Mg quaternary eutectic alloy. The bulk growth rates were also determined lambda(2)(si) V = 92.24, lambda(2)(CuAl2) = 669.2, and lambda(Cu2Mg8Si6Al5) V = 4205.5 mu(3)/s by using the measured values of lambda Mg2Si, lambda(CuAl2), lambda(Cu2Mg8Si6Al5), and V for the Si plates and intermetallic Al2Cu (theta) and Cu2Mg8Si6Al5 (Q) phases in the Al-Cu-Si-Mg eutectic alloy, respectively. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Directional solidification; Quaternary eutectic alloy; Aluminium alloy; Microstructure; Electrical properties; GROWTH-RATE; MECHANICAL-PROPERTIES; TEMPERATURE-GRADIENT; MICROHARDNESS; SPACINGS; UNDERCOOLINGS; STRENGTH; ALUMINUM; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering